Hypoehoic lesions on Transrectal Ultrasound and its correlation to Gleason grade in the diagnosis of Clinically Significant Prostate Cancer: A Prospective Study - Sharma, Manas; Nerli, Rajendra B.; Nutalapati, Sree Harsha; Ghagane, Shridhar C. (South Asian Journal of Cancer, 2021)
Context The importance of hypoechoic lesions on transrectal ultrasound (TRUS) merits re-assessment in the present era of widespread prostate-specific antigen (PSA) testing.Aims We aimed to investigate the predictive accuracy of hypoechoic lesions on TRUS of prostate in the diagnosis of prostate cancer and to examine the association of hypoechoic lesions with the aggressiveness of prostate cancer.Settings and Design This prospective study was conducted in a tertiary care center in South India from November 2017 to December 2019.Methods and Material We included 151 patients undergoing TRUS-guided 12-core prostate biopsy in view of raised serum PSA with or without suspicious digital rectal examination (DRE) findings in the study. Age, DRE findings, serum PSA level, TRUS findings, and histopathology reports were documented. These were compared between patients with and without hypoechoic lesions on TRUS.Statistical Analysis Used The statistical analysis for this study was performed using SPSS v20.0 software.Results Among 151 men, prostate cancer was diagnosed in 68 (45.03%) with mean age at presentation 69.81 ± 6.49 years. Fifty-eight cases (38.41%) had hypoechoic lesion on TRUS and the cancer detection rate (68.96%) amongst this group was significantly higher than in those without hypoechoic lesion (p <0.0001). Patients with hypoechoic lesion were more likely to have higher grade cancer. Abnormal DRE findings and hypoechoic lesion on TRUS were independent predictors of a clinically significant cancer (p <0.05).Conclusion Hypoechoic lesion on TRUS can be considered as an indicator of clinically significant prostate cancer.
Keywords: prostate cancer; transrectal ultrasonography; prostate biopsy; hypoechoic lesion